Multicentric Castleman's disease developing during follow‐up of sarcoidosis. Issue 4 (28th May 2016) - Sawata, Tetsuro; Bando, Masashi; Nakayama, Masayuki; Mato, Naoko; Takemura, Tamiko; Sugiyama, Yukihiko
Abstract: Pulmonary sarcoidosis is reported to have complication of lymphoproliferative disease such as malignant lymphoma, but the complication of multicentric Castleman's disease (MCD) is rarely reported. In our case of a 60‐year‐old woman, bilateral hilar lymphadenopathy was noted in her chest X‐ray. We performed a transbronchial lung biopsy. She was diagnosed as having pulmonary sarcoidosis (Stage II). The shadow on chest X‐ray disappeared without treatment. However, after 8 years, swelling of the mediastinal and abdominal lymph node, thickened bronchovascular bundle, and multiple nodular shadows were identified, and a thoracoscopic lung biopsy was performed. Based on the histopathological findings and elevated serum interleukin‐6 level (75.7 pg/mL), she was diagnosed with pulmonary sarcoidosis complicated by MCD. When a change in chest X‐ray findings are found during monitoring of pulmonary sarcoidosis, it is important to proceed with a thoracoscopic lung biopsy, because of the possibility of the rare complication of MCD. Abstract : We identified a case of multicentric Castleman's disease (MCD) while monitoring the progress of a patient with pulmonary sarcoidosis. The complication of pulmonary sarcoidosis and MCD is rare. When radiological changes are found during monitoring of pulmonary sarcoidosis, it is important to proceed with a lung biopsy.